A data de nascimento de Afonso I - Abel Estefânio (Medievalista)
Despite the challenge that is always an enigma, the contradiction between the sources of the date of birth of Afonso Henriques had never been properly studied because it is not considered a matter of history, little concerned with the investigation of isolated facts from the past. No wonder that this article arise in the margins of professional historiography, despite having been the recent publication of the biography of D. Afonso Henriques, who came to renew the interest in the subject. The aim of this paper is to revisit the coeval sources in light of the problem. We intend to show that “Vita Theotonii” is not only the primary source but also contains within itself the «original sin» upon which was settled the confusion over the date of birth of our first king, which lasted until the present. The explicit purpose eventually had become a plea for a broader discussion of the problems of textual transmission.